Alfadatizando 2.0 applied to data visualization at high school level and for digital humanities: empowering digital citizens - Lliteras, Alejandra Beatriz (2025)
Given the great evolution and transformation of digital technologies and their penetration in different aspects of daily life, there is a need to provide equal possibilities and equal rights to access them, which implies training digi-tal citizens. On the other hand, digital technology and some methods of social sciences and computer science to visualize data, support what is known as digi-tal humanities. These add computational thinking and create new kinds of jobs, skills and specific knowledge. Currently there are several efforts to add their teaching at the higher level, however, there is little evidence of their presence at the high school level. With the aim of promoting the formation of digital citi-zens by considering aspects of computational thinking through data visualiza-tion in digital humanities, this paper first analyzes articles that consider the teaching of digital humanities in order to know the visualization methods ap-plied. A platform to make educational activities considering some of the sur-veyed methods is presented, a case study considering a curricular design is pro-posed and a proof of concepts from the above is performed. The results of the survey analysis show, on the one hand, the use of certain data visualization methods in the teaching of digital humanities at high school level, on the other hand, the feasibility of using the proposed platform for the defined case study and the viability to develop digital skills and computational thinking in students. This is considered a contribution to the empowerment of digital cit-izens from the high school level.